Audiometric testing and hearing protection training through multimedia technology. - Hong O; Csaszar P (International Journal of Audiology, 2005)
The purpose of this paper is to present the development process of a computer-based audiometric testing and tailored intervention program, and assess its feasibility by obtaining users' feedback. The program was implemented for 397 operating engineers at their union training center, and its feasibility was evaluated by obtaining quantitative and qualitative feedback from the participants through a survey and focus group. Over 96% of the participants indicated they liked receiving a hearing test by computer; the computer-based test worked smoothly; and the computer-based training was well organized, effective and held their interests. Almost all (more than 99%) said they would recommend this program to other workers. This project is considered as one of the first ones incorporating multimedia computer technology with self-administered audiometric testing and tailored training. Participants' favorable feedback strongly supported the continued utilization of this approach for designing and developing health screening and intervention to promote healthy behaviors.